International Trade and Business in The Late 1980s: An Integrated U.S. Perspective - Czinkota, Michael R. (Journal of International Business Studies, 1986)
Much of the current research and teaching in international business and trade is not part of a concerted effort in a given direction. This is the result of a lack of adequate information about what the major issues will be, and a lack of adequate communication between the academic, business, and policymaking communities. This article presents the findings of a Delphi study conducted with academicians, business executives, and policymakers involved in international trade. The most crucial issue identified by that research is the current challenge to the multilateral trade framework. This challenge emanates from such new factors as trade in services, subsidization, high technology transfer, countertrade, and orderly marketing agreements. After discussing these and other newly emerging issues in international business and trade, recommendations are made to encourage a better focus for future research and teaching in the international business and trade arena.